Behavior factor evaluation of CFS wood sheathed shear walls according to FEMA P695 for Eurocodes. (15th October 2020) - Shakeel, Sarmad; Fiorino, Luigi; Landolfo, Raffaele
Highlights: Seismic response of CFS shear walls with wood sheathing is evaluated following FEMA P695 methodology. 3-Dimensonal models of two fourteen set of archetypes are developed. The model of shear walls possesses the ability to simulate nonlinear deteriorating hysteretic behaviour. A value of 2.5 for behavior factor is proposed for CFS shear walls with wood sheathing. Abstract: Cold formed steel (CFS) wood sheathed shear walls are one of the most often used type of shear walls applied as the main lateral force resisting system (LFRS) in a lightweight steel (LWS) building. This paper evaluates the behavior factor used in the seismic design according to Eurocodes for buildings equipped with CFS wood sheathed shear walls as the main LFRS. FEMA P695 methodology is used to evaluate the behavior factor. A set of archetypes are selected and designed, which reflected the applicable building heights, seismic hazard and occupancies for LWS buildings in Europe. Nonlinear three-dimensional finite element (FE) models of building archetypes are developed in OpenSees software using the individual shear wall models, which are calibrated on results from tests on individual shear wall specimens. The resilience of building models against collapse is checked by analyzing the models using lateral static (pushover) and incremental dynamic analysis (IDA). Uncertainties arising from test and design information, numerical modelling and archetype response variability to different ground motions is also taken into account. Based on the collapse performance evaluation results, a value of 2.5 for behavior factor, used in the design, is found to provide appropriate level of safety against the collapse in LWS buildings equipped with CFS wood sheathed shear walls.